A Comprehensive Review of Diabetic Retinopathy and Diabetic Macular Edema from an Ayurveda Point of View - Tripathi, Ankur; Fiaz, Shamsa; Sharma, Swati (International Research Journal of Ayurveda & Yoga, 2023)
Introduction: Diabetes and other related disorders, such as hypertension, are involved in diabetic retinopathy (DR), a chronic, progressive disease of the retinal microvasculature that threatens vision. The retinal pre-capillary arterioles, capillaries, and venules are impacted by DR. Hyperglycemia damages capillary walls, endothelial cells, retinal cells, and capillary pericytes. It also thickens the capillary basement membrane. The blood-retina barrier is broken down by microangiopathy, which can result in retinal edema, bleeding, lipid leakage (hard exudates), micro-aneurysms, hemorrhages, ischemia, and intraretinal microvascular abnormalities. Materials and Methods: Ayurveda classical texts along with the internet sources such as Google Scholar and PubMed were reviewed upon to collect the literature available as per the aims of the present article. Discussion and Conclusion: In Ayurveda, DR can be understood as Pramehajanya Timira. Due to prolonged uncontrolled hyperglycemia, two types of pathology in Madhumeha: Dhatukshayajanya and Avaranajanya play a crucial role in the development of DR. Dhatus are expelled from the body in Dhatukshaya, which leads to several pathogenic events and the development of DME. Attipravritti, Sanga, Siragranthi, and Vimarga Gamana are the four varieties of Srotodusti that are known to be important in the development of DR and macular edema.